(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Remittance as a main cause of foreign currency to the rising nation hasbecome a considerable component of making current account surplus in thebalance of payments. It is argued that many workers from Nepal going abroad foremployment are no doubt young, energetic, laborious and enthusiastic. Thesocial impacts of such migration were likely to be at least as profound as thefinancial ones, particularly with regard to family and gender relations. Insome Nepalese villages, up to 90% of the young men have left, returning at mostevery six months. This paper discusses the various aspects of remittancerelated to capital accumulation, spending pattern, contribution to the economyas well as the possibility of economic failure due to burgeoning dependency onit.